Governança conflitiva das fronteiras marítimas, securitização e migração irregular - Matos, Ana Carolina Barbosa Pereira (2019)
In the last decades, technological advances have diminished distances in many ways, making mass migration a reality in many parts of the world. On the other hand, the concern with the external borders of the States and the discourses of criminalization of the figure of the immigrant grew, which culminated in the securitization of migratory movements. Faced with this reality, the thesis defended is that the relationship established between the State management of migrats flows and the ‗boat‘ migrants rights has been based on a model of conflictive governance, given the preponderance of the forces of security as the main interlocutor of immigration policies, to the detriment of the rights of migrants that are in transit. The general objective of this research will be to verify the existence of limits imposed on the exercise of state sovereignty over human mobility, in other words, in which situations the observance of human rights must surpass the sovereignty of States with regard to migrants by sea, in order to to verify the possibility of overcoming the conflictive governance model. The phenomenon of migrations by the sea and the risks inherent in them are not a problem restricted to a single continent. These issues, however, have so far not received appropriate international treatment. Thousands of lives of migrants have already been lost at crossings across the world as a result of border control strategies practiced by many States. Therefore, the urgency of the proposed research is verified in order to make it possible to reformulate migratory policies at the international level. Regarding the method of investigation adopted, the research is developed from the inductive method, being carried out a bibliographical, documentary and jurisprudential analysis. The development of this work is divided into four chapters. The first part analyzes the relationship established between sovereignty and immigration and how it is legitimized by international security. In the second chapter, it is sought to verify if the measures of securitization of vulnerable at sea adopted by developed coastal States should be considered as an expression of the regular exercise of State sovereignty or an offense to the human right of freedom of movement. In the next chapter, it is investigated whether migrants by sea have a human right to migrate or whether migrants have only immigration rights. The last chapter, analyzes if the problem faced in this work would be a problem of governance or a problem of lack of rights, proposing, in the end, possible solutions based on soft law norms. It was concluded that refugee law should be considered as the minimum threshold to be respected by the signatory States of the 1951 Convention, as well as by any State regarding the principle of non-refoulement, in the establishment of migration policies. Thus, it is essential to expressly acknowledge the need to comply with these rights in the soft standard documents that are proposed to establish a migratory governance, considering that the right to seek asylum is a relevant mitigation to the exercise of State sovereignty over migratory issues.